2003
DOI: 10.1097/00041552-200309000-00006
|View full text |Cite
|
Sign up to set email alerts
|

The renal cell primary cilium functions as a flow sensor

Abstract: The primary cilium is mechanically sensitive and serves as a flow sensor in cultured renal epithelia. Bending the cilium by mechanical means or flow causes a large, prolonged transient increase in intracellular calcium. The mechanically sensitive protein in the cilium is a polycystin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
169
0
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 243 publications
(171 citation statements)
references
References 20 publications
0
169
0
2
Order By: Relevance
“…Although the linear dependence of reabsorption on microvillous torque is reassuring, this issue is difficult to resolve with certainty because of the positive correlation of hydrodynamic drag on both microvilli and cilia. Our data show that increased torques on the microvilli produced a stimulation of Na ϩ transport, whereas the torques on the cilia should lead to a decrease in absorption because the bending of the cilia causes an increase in intracellular Ca 2ϩ through stretchactivated ion channels (28). The increased intracellular Ca 2ϩ will produce an inhibition of Na ϩ and HCO 3 Ϫ absorption in proximal tubules (30).…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Although the linear dependence of reabsorption on microvillous torque is reassuring, this issue is difficult to resolve with certainty because of the positive correlation of hydrodynamic drag on both microvilli and cilia. Our data show that increased torques on the microvilli produced a stimulation of Na ϩ transport, whereas the torques on the cilia should lead to a decrease in absorption because the bending of the cilia causes an increase in intracellular Ca 2ϩ through stretchactivated ion channels (28). The increased intracellular Ca 2ϩ will produce an inhibition of Na ϩ and HCO 3 Ϫ absorption in proximal tubules (30).…”
Section: Discussionmentioning
confidence: 73%
“…In contrast to the mechanosensory function of microvilli proposed for the proximal nephron, flow-dependent transport in the distal nephron has recently been attributed to renal epithelial cilia (28). Subsequently, Liu et al (29) demonstrated that flowdependent increases in [Ca 2ϩ ] i occur in both principal cells with apical cilia and intercalated cells with apical microvilli or microplicae that lack cilia, suggesting that these intercalated cell projections also serve a mechanosensory function.…”
Section: Discussionmentioning
confidence: 99%
“…While the exact function of the immotile, primary cilium of kidney epithelial cells is not well understood, it is now well established that loss of ciliary function and/or formation results in cystic diseases pointing to a central role of this organelle in PKD pathophysiology [50,51]. Because cilia function as sensory organelles in the olfactory and vision systems [52], it is believed it may have a similar sensory function in the renal epithelial cells [53,54]. Such a function could be fluid flow sensing [54].…”
Section: Function At the Primary Ciliummentioning
confidence: 99%
“…Because cilia function as sensory organelles in the olfactory and vision systems [52], it is believed it may have a similar sensory function in the renal epithelial cells [53,54]. Such a function could be fluid flow sensing [54]. In support of this hypothesis, it has been shown that mechanical bending of the primary cilium or fluid flow in MDCK cells resulted in increases in intracellular Ca 2+ concentration which was dependent on extracellular Ca 2+ , PLC activation and inositol 1,4,5 trisphosphate (IP 3 )-induced release of intracellular Ca 2+ stores [55][56][57].…”
Section: Function At the Primary Ciliummentioning
confidence: 99%
“…Cilia serve as a cell's "antenna" to sample a broad range of extracellular signals in olfaction, vision, taste, and mechanosensation (4,5). Primary cilia of kidney epithelia are mechanosensitive, detecting fluid flow through the tubule (6). Cilia of olfactory epithelia distinguish a large number of odorants (7).…”
mentioning
confidence: 99%